2017
DOI: 10.1080/15569527.2017.1317783
|View full text |Cite
|
Sign up to set email alerts
|

The effects of smoking on corneal endothelial cells: a cross-sectional study on a population from Isfahan, Iran

Abstract: Our study showed that smoking can cause significant changes in some of the corneal endothelial variables, but not all of them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 30 publications
0
25
1
Order By: Relevance
“…This leads to tachycardia and increased peripheral resistance. It also stimulates adrenal gland causing more cardiovascular effects [13]. Carbone monoxide (CO) is as high as 100folds higher in smokers comparing with nonsmokers; leading to increment of carbo-…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This leads to tachycardia and increased peripheral resistance. It also stimulates adrenal gland causing more cardiovascular effects [13]. Carbone monoxide (CO) is as high as 100folds higher in smokers comparing with nonsmokers; leading to increment of carbo-…”
Section: Resultsmentioning
confidence: 99%
“…xyhemoglobin and increases tissue hypoxia [13,14]. The corneal endothelial layer plays an indispensable role in keeping the corneal transparency and preservation of vision [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among our patients, smoking was significantly more common, defined as pack/years, in the moderate-severe COPD group. Golabchi et al reported that smoking results in an increased CV and decreased ECD (15). Ilhan et al (16) reported that smoking does not affect the CCT, CV, and percentage of hexagonality values, but there was a significant reduction in ECD in smokers.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Kara and colleagues 10 reported that CS affects the tear break-up time, but no significant differences in the mean central corneal thickness (CCT), mean CEC density, or parameters of endothelial cell morphology were observed between smokers and non-smokers. 10 In another study, Golabchi and colleagues 11 documented that smokers with severe nicotine dependency had substantially greater average cell size and lower CEC density as compared to nonsmokers.…”
mentioning
confidence: 98%